2019
DOI: 10.1111/iej.13138
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and antiresorptive functions of melatonin on experimentally induced periapical lesions

Abstract: Aim To investigate the effects of systemically administered melatonin on inflammation and alveolar bone resorption in rats with experimentally induced periapical lesions. Methodology Thirty adult Sprague Dawley rats were divided equally into negative, positive control and melatonin groups. The pulp chambers of their mandibular first molars were exposed to the oral environment to induce experimental periapical lesions in the positive control and melatonin groups. The melatonin group received daily intraperitone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 50 publications
(108 reference statements)
3
26
0
3
Order By: Relevance
“…injection of melatonin (10 mg/kg) for 21 days, radiological periapical bone loss and osteoclasts were decreased, the OPG level was increased, and the IL-1β, RANK and RANKL levels were decreased, as compared with the positive control. In addition, the bacteria localization score has been shown to be significantly lower following melatonin treatment (130). Renn et al (131) reported that preventive melatonin supplementation suppressed the Toll-like receptor 4/myeloid differentiation factor 88 pathway to inhibit the activation of pro-inflammatory cytokines and normalize the balance between RANKL and OPG, thus suppressing the progression of periodontitis.…”
Section: Time Ofmentioning
confidence: 99%
“…injection of melatonin (10 mg/kg) for 21 days, radiological periapical bone loss and osteoclasts were decreased, the OPG level was increased, and the IL-1β, RANK and RANKL levels were decreased, as compared with the positive control. In addition, the bacteria localization score has been shown to be significantly lower following melatonin treatment (130). Renn et al (131) reported that preventive melatonin supplementation suppressed the Toll-like receptor 4/myeloid differentiation factor 88 pathway to inhibit the activation of pro-inflammatory cytokines and normalize the balance between RANKL and OPG, thus suppressing the progression of periodontitis.…”
Section: Time Ofmentioning
confidence: 99%
“…Additionally, Saritekin et al . (2019) demonstrated that the administration of melatonin decreases the inflammatory process and bone destruction in periapical lesions caused experimentally in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The borders of the radiographic lesions of the mesial root canals were marked. The total area of the lesions was calculated (mm 2 ), also verified in pixels, and compared between groups (Sarıtekin et al, 2019). All radiographs of right hemimandibles were coded randomly ordered and analysed using the ImageJ program by two independent blinded authors.…”
Section: Methodsmentioning
confidence: 99%